2022
DOI: 10.26740/bisma.v15n1.p20-39
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and consequences of value co-creation in online shopping

Abstract: Customer involvement is necessary for the value co-creation process in online purchases. This study intends to confirm the effect of online shopping experience on customer value co-creation behaviour, represented by participation behaviour and customer citizenship behaviour on repurchase intention and negative electronic word-of-mouth (eWOM). An online survey was conducted to collect data from the customers as respondents. This study used Partial Least Square-Structural Equation Modelling (PLS-SEM) to test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…Fast and reliable delivery services, coupled with responsive customer support, contribute positively to overall customer satisfaction and loyalty (Muharam et al, 2021). The SERVQUAL model is in line with this study, which emphasizes the importance of service quality in e-commerce platforms (Sanaji et al, 2022). The study also found that ease of use has the greatest impact on customer satisfaction (Wulandary et al, 2023).…”
Section: Service Quality and Customer Loyaltysupporting
confidence: 68%
“…Fast and reliable delivery services, coupled with responsive customer support, contribute positively to overall customer satisfaction and loyalty (Muharam et al, 2021). The SERVQUAL model is in line with this study, which emphasizes the importance of service quality in e-commerce platforms (Sanaji et al, 2022). The study also found that ease of use has the greatest impact on customer satisfaction (Wulandary et al, 2023).…”
Section: Service Quality and Customer Loyaltysupporting
confidence: 68%